Optimizing Lean University Services Through UI/UX Design Using a User Centered Design Approach in Rokan Hulu - Utami, Urfi; Kurniawan, Hendry; Andrianto, Richi; Yona, Sri Nelvi; Wati, Emilia (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
Digital transformation in higher education demands efficient and user-centered digital service systems, particularly in regional universities where service processes are often fragmented, manual, and insufficiently aligned with user needs, such as in the context of Rokan Hulu. Existing studies predominantly address User Centered Design (UCD) or Lean Service separately, leaving a research gap in their integrated application for optimizing university digital services in developing regions. This study aims to bridge this gap by proposing an integrated UCD–Lean framework to redesign UI/UX and streamline service workflows based on empirical user needs and operational efficiency principles. The research adopts a four-stage UCD methodology consisting of context of use analysis through observations and semi-structured interviews with students, lecturers, and administrative staff; requirement specification using user personas and journey mapping; iterative design solutions developed through wireframes and interactive prototypes in Figma; and usability evaluation. Lean principles were operationalized through workflow simplification, elimination of non–value-added steps, and value-oriented interaction design. A purposive sample of 100 respondents representing primary academic service users in Rokan Hulu participated in usability testing using the System Usability Scale (SUS), selected for its reliability in prototype-level assessment. The results show a mean SUS score of 80 (“Good”), indicating acceptable usability and positive user acceptance, while the study theoretically contributes a contextual UCD–Lean integration model and positions its findings as preliminary usability evidence rather than definitive operational effectiveness due to prototype-based evaluation limitations.